2016
DOI: 10.1093/jisesa/iew076
|View full text |Cite
|
Sign up to set email alerts
|

Co-Infestation and Spatial Distribution ofBactrocera carambolaeandAnastrephaspp. (Diptera: Tephritidae) in Common Guava in the Eastern Amazon

Abstract: Field infestation and spatial distribution of introduced Bactrocera carambolae Drew and Hancock and native species of Anastrepha in common guavas [Psidium guajava (L.)] were investigated in the eastern Amazon. Fruit sampling was carried out in the municipalities of Calçoene and Oiapoque in the state of Amapá, Brazil. The frequency distribution of larvae in fruit was fitted to the negative binomial distribution. Anastrepha striata was more abundant in both sampled areas in comparison to Anastrepha fraterculus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 47 publications
(62 reference statements)
1
15
0
3
Order By: Relevance
“…During this study, several mango fruits were infested by both species (B. dorsalis and C. cosyra). Recent studies have reported the co-infestation of guava (Psidium guajava) with an introduced species Bactrocera carambolae and native species of the genus Anastrepha in Brazil [11] and Ceratitis capitata (introduced species) and Anastrepha fraterculus (native species) in Argentina [8] [12].…”
Section: Discussionmentioning
confidence: 99%
“…During this study, several mango fruits were infested by both species (B. dorsalis and C. cosyra). Recent studies have reported the co-infestation of guava (Psidium guajava) with an introduced species Bactrocera carambolae and native species of the genus Anastrepha in Brazil [11] and Ceratitis capitata (introduced species) and Anastrepha fraterculus (native species) in Argentina [8] [12].…”
Section: Discussionmentioning
confidence: 99%
“…Aggregations among A. fraterculus, A. striata and Bactrocera carambolae were recently observed in guava in eastern Amazonia. These interactions followed a negative binomial distribution pattern, suggesting that the species coexist in that region (DEUS et al, 2016).…”
Section: Overlap Patternmentioning
confidence: 94%
“…Studies of the interactions of Anastrepha species in their niches have generally been neglected and have only recently been carried out in Brazil (LOPES et al, 2015;DEUS et al, 2016). In general, studies on the population dynamics of fruit lies are related to faunal analyses and without regard to interspeciic competition.…”
Section: Introductionmentioning
confidence: 99%
“…Tilman (1994) proposed that coexistence of species is favoured by environmental disturbance if it empties (at least partially) the niche, or even generates new niches. Biological invasions can lead to the displacement of the indigenous species, or, alternatively, to a stable coexistence of the involved species under tolerable levels of competition (Human & Gordon, 1996;Juliano, 1998;Amarasekare, 2002;Braks et al, 2004;Duyck et al, 2007;Perdereau et al, 2011;Deus et al, 2016). Interspecific competition derived from situations in which a new species is introduced is not uncommon (Fitt, 1989;Duyck et al, 2004Duyck et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Interspecific competition derived from situations in which a new species is introduced is not uncommon (Fitt, 1989;Duyck et al, 2004Duyck et al, , 2006. Biological invasions can lead to the displacement of the indigenous species, or, alternatively, to a stable coexistence of the involved species under tolerable levels of competition (Human & Gordon, 1996;Juliano, 1998;Amarasekare, 2002;Braks et al, 2004;Duyck et al, 2007;Perdereau et al, 2011;Deus et al, 2016).…”
Section: Introductionmentioning
confidence: 99%